1984
DOI: 10.1128/mcb.4.3.387-398.1984
|View full text |Cite
|
Sign up to set email alerts
|

How Damaged is the Biologically Active Subpopulation of Transfected DNA?

Abstract: Relatively little is known about the damage suffered by transfected DNA molecules during their journey from outside the cell into the nucleus. To follow selectively the minor subpopulation that completes this journey, we devised a genetic approach using simian virus 40 DNA transfected with DEAE-dextran. We investigated this active subpopulation in three ways: (i) by assaying reciprocal pairs of mutant linear dimers which differed only in the arrangement of two mutant genomes; (ii) by assaying a series of wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…On the basis of analysis of the alphoid tetO -HAC structure, we propose a mechanism for its de novo formation in human cells from a synthetic alphoid DNA array (Figure ), the initial steps of which may be general for all HACs developed from different alphoid DNA arrays. This mechanism is very similar to those proposed to describe the fate of exogenous DNA following its transfection into mammalian cells, a process known to be accompanied by a high frequency of structural rearrangements, including both degradation and generation of concatamers. , Stable transfection of cells is typically achieved by integration of multiple copies of input DNA into host chromosomes . Indeed, such integrants typically represent up to 80% of all clones selected during HAC formation. ,,,,, …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…On the basis of analysis of the alphoid tetO -HAC structure, we propose a mechanism for its de novo formation in human cells from a synthetic alphoid DNA array (Figure ), the initial steps of which may be general for all HACs developed from different alphoid DNA arrays. This mechanism is very similar to those proposed to describe the fate of exogenous DNA following its transfection into mammalian cells, a process known to be accompanied by a high frequency of structural rearrangements, including both degradation and generation of concatamers. , Stable transfection of cells is typically achieved by integration of multiple copies of input DNA into host chromosomes . Indeed, such integrants typically represent up to 80% of all clones selected during HAC formation. ,,,,, …”
Section: Resultssupporting
confidence: 55%
“…This mechanism is very similar to those proposed to describe the fate of exogenous DNA following its transfection into mammalian cells, a process known to be accompanied by a high frequency of structural rearrangements, including both degradation and generation of concatamers. 44,45 Stable transfection of cells is typically achieved by integration of multiple copies of input DNA into host 46 Indeed, such integrants typically represent up to 80% of all clones selected during HAC formation. 2,4,6,16,22,27−31 We suggest that during transfection, multiple alphoid tetO vector molecules penetrate some of the target cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When considering the length of RmI sequences present in the recombinants, we found that there was a wide variation ranging from a few hundred base pairs to almost the entire 7,100-bp molecule, with a uniform distribution of the various lengths (data not shown). This suggests that if nonhomologous recombination is the result of end-to-end ligation as has been suggested (12,48), then the vast majority of parental molecules are subjected to degradation or breakage before ligation. Another consideration is that the homologous sequences of both parental molecules can be readily maintained in a nonhomologous recombinant.…”
Section: Resultsmentioning
confidence: 94%
“…The fact that cotransfection with circular molecules gives homologous recombinants with the same overall structure, as with one or both parental molecules being linear, suggests that double-strand breaks are part of the recombination mechanism. Wake et al (48) have evaluated that each 5 to 15 kbp of transfected DNA is subjected to a double-strand break. If these double-strand breaks are in or near the homologous sequences, this could lead to pairing between homologous sequences sharing an overlap, resulting in a junction of the type proposed by Lin and colleagues (21) and Wake and colleagues (49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation